Keanekaragaman Serangga Hama Pada Budidaya Padi Dengan dan Tanpa Rekayasa Ekologi - Yuni Ratna; Wilma Yunita; Bayu Pambudi (Jurnal Media Pertanian, 2023)
This research was carried out on rice fields belonging to farmer in Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency, Jambi Province. The insects found were identified at the Plant Pest Laboratory, Faculty of Agriculture, Jambi University. This study aimed to examine the effect of the application of ecological engineering in rice cultivation on the diversity of rice plant insects. This research was carried out by comparing ecologically engineered rice cultivation techniques with conventional rice cultivation techniques usually used by farmers. There were two experimental plots each for ecological engineering and conventional cultivation techniques with an area of each plot of + 0.65 ha. There were five sample plots measuring 25 m2 which were placed diagonally in each experimental plot. Sesame (Sesamum indicum) and Tagetes sp. used as flowering plants. The variables observed were the species of insects that have the potential to become pests and the percentage of dominant pest attacks. The species and populations of pests as well as the percentage of infected plants were analyzed descriptively. Based on research results, the species of insects that have the potential to become pests were found to be more numerous in conventional rice cultivation (16 species) than in ecological engineering (14 species). The population and attacks of Cnaphalocrosis medinalis were higher in conventional rice cultivation than ecologically engineered rice cultivation, however, the population and attacks of Leptocorixa oratorius were higher in ecologically engineered rice cultivation than conventional rice cultivation.